SCIENTIFIC AND THEORETICAL METHODOLOGICAL FOUNDATIONS OF THE USE OF FOLK ORAL LITERATURE IN THE CREATIVE ACTIVITIES OF FUTURE TEACHERS. (Multidisciplinary Journal of Science and Technology, 2026)
This article presents ideas on determining the level of pedagogical and creative activity of the methodology of teaching the creative activity of a future primary school teacher through the use of folk art. Issues of studying the factors and tools influencing the improvement of the methodology of teaching the creative activity of a primary school teacher through the use of folk art are revealed